Novel Method for Fabrication of Super-Hydrophobic Film on Magnesium Alloy and Consequent Anticorrosion Performance - Min, Liyuan; Zhang, Runhu (Asian Journal of Chemistry, 2015)
A novel two-step dipping method has been proposed to fabricate super-hydrophobic film on magnesium alloy with hexamethylene-diisocyanate trimer (HDI trimer) and laurylamine. With this method, super-hydrophobic film, which is composed of HDI trimer-laurylamine biuret, can be fabricated on metal surface within 10 sec. The film morphologies and chemical compositions were investigated using scanning electron microscope and Fourier-transform infrared spectrophotometer. It is shown that rough micro-structure and low surface energy of biuret film confer super-hydrophobicity of resultant film. The concentrations of HDI trimer and laurylamine are investigated to determine their effects on wettability of film. Furthermore, the anticorrosion performance and mechanism of super-hydrophobic film to magnesium alloy in 3.5 % NaCl solution are studied with electrochemical measurements. It is proven that super-hydrophobic film can protect underlying magnesium alloy effectively and the air trapped in film is the main contributor for the barrier performance.